Magnetoresistance of granular high-temperature superconductor YBa₂Cu₃O₇-delta in weak magnetic fields - Derevyanko, V.V.; Sukhareva, T.V.; Finkel, V.A. (Functional Materials, 2004)
The transverse and longitudinal magnetoresistance ∆ρ/ρ₂₇₃ K(H) of ceramic samples of the high-temperature superconductor YBa₂Cu₃O₇-δ was studied experimentally at T = 77.3 K in the magnetic fields 0 < H < 500 Oe. A phenomenon was found of a jumping variation of the magnetoresistance in the magnetic fields H = Hjump that was associated with alteration of the vortex structure. The magnetoresistance field dependence is shown to be of hysteresial nature. The presence of an alignment dependence was found of the value of the magnetoresistance and critical fields of the weak links and superconducting granules (Hc2j, HclA and Hjump), as well as the dependence of the value of the critical fields Hc2j, Hc1A and Hjump, vs. the transport current density and preceding magnetic history. Экспериментально изучено поперечное и продольное магнитосопротивление ∆ρ/ρ₂₇₃ K(H) керамических образцов высокотемпературного сверхпроводника YBa₂Cu₃O₇-δ при T = 77.3 K в магнитных полях 0 < H < 500 Oe. Обнаружен эффект скачкообразного изменения магнитосопротивления в магнитных полях H = Hjump, связанный с перестройкой вихревой структуры. Показано, что полевая зависимость магнитосопротивления носит гистерезисный характер. Обнаружено наличие ориентационной зависимости величины магнитосопротивления и критических полей слабых связей и сверхпроводящих гранул (Hc2j, Hcia и Hjump) и зависимости величины критических полей Hc2j, Hcia и Hjump от плотности транспортного тока и магнитной предыстории. Експериментально вивчено поперечний i подовжній магнітоопір ∆ρ/ρ₂₇₃ K(H) керамічних зразків високотемпературного надпровідника YBa₂Cu₃O₇-δ при Т = 77.3 K у магнітних полях 0 < H < 500 Oe. Виявлено ефект стрибкоподібної зміни магнітоопору у магнітних полях H = Hjump, пов’язаний з перебудовою вихрової структури. Показано, що польова залежність магнітоопору носить гістерезисний характер. Виявлено наявність орієнтаційної залежності величини магнітоопору і критичних полів слабких зв’язків і надпровідних гранул (Hc2j, HclA i Hjump) i залежності величини критичних полів Hc2j, HclA i Hjump від щільності транспортного струму і магнітної передісторії.